Seniman Pauh Frozen online ordering system / Mohamad Asnuramzan Mohamad Yasin - Mohamad Yasin, Mohamad Asnuramzan (2023)
The Seniman Pauh Frozen Online Ordering System is a prototype of the frozen food online ordering system that will be used by Seniman Pauh Frozen Sdn Bhd, which is based in Rawang, Selangor. Initially, the system would allow customers to place orders for the company's products online. The company faced higher overhead costs in paying employees’ salaries. The company needs to hire more employees if the company wants more customers to buy the product in this physical store. Also, every branch has limited space to display the product including the quantity of stock and keeps an inefficient record of the customers' purchases. The objective of this project is to study and understand the current business process and user requirements of the system. Also, to design and developed a system for Seniman Pauh Frozen Sdn Bhd and to evaluate the system functionality and usability of e-commerce. The Adapted Waterfall Model was used in the development of this prototype system, and it consists of six different stages in sequential order. System planning, requirement analysis, design, development, testing, and documentation are the stages that are included in this process. In addition, the developer uses the Ten Usability Heuristics as a theory that acts as a guideline for the development of the Seniman Pauh Frozen Online Ordering System. To ensure that the functioning of the system satisfies all of the requirements, a test plan has been developed and made available to the customers, the staff, and the admin. In addition to that, a limited group of users and an expert have reviewed this system, and the input that they provided has been taken into account. All of the recommendations and enhancements that were collected throughout the testing session can serve as a reference for upcoming work that aims to improve the system's usability and functionality. It is hoped that the current business process of Seniman Pauh Frozen Sdn Bhd will be improved with the implementation of the Seniman Pauh Frozen Online Ordering System.